Relationship Between Diet with the Incidence of Gastritis at Patients Treated Roads the Internal Disease Poly Hospital Dr. R. Koesma Tuban - nikita welandha prasiwi (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
ABSTRACT Gastritis is one of the health problems that exist in the community. In 2012, gastritis ranked sixth among other diseases. In Internal Disease poly at Hospital Dr. R. Koesma Tuban, an increase in cases of gastritis since last 5-6 years. A good diet is one of the treatment of gastritis and is apreventive measure to prevent the occurrence of gastritis. The purpose of this study is to determine the relationship between diet and the incidence of gastritis in patients who visited the Internal Disease poly at Hospital Dr. R. Koesma Tuban. The design of this study is the population Correlational studies and obtained a sample 110 respondents of 150 respondents. The sampling technique is using acidental sampling. Collecting data is using a questionnaire. Data were analyzed using Phi coefficient test with a significant level of α = 0.05. Based on the results, 45 (67,2%) of respondents who experienced gastritis have a poor diet, and 26 (60,5%) of respondents who do not gastritis have a good diet. The results of the analysis using the Phi coefficient test in get p = 0.004. p α then means H0 is rejected, so there is a relationship between diet and the incidence of gastritis. From the description above it can be concluded that in order to increase the awareness of the community to implement a good diet, counseling or health education on the importance of diet to disease gastritis health workers need to be given in order to prevent and reduce cases of gastritis.